THE LEGAL STATUS OF THE USE OF ASSISTED REPRODUCTIVE TECHNOLOGY IN DETERMINING LINEAGE AND INHERITANCE RIGHTS: A MAQĀṢID AL-SHARĪ‘AH ANALYSIS - Mubarak, Azzam Zuhdi; Haq, Yusdi (Program Pascasarjana UIN Sumatera Utara, 2026)
Assisted Reproductive Technology (ART) offers infertile couples an opportunity to have children but raises legal issues concerning lineage and inheritance rights. This study analyzes the legality of ART, the lineage and inheritance status of children born through different ART procedures, and their assessment from the perspective of maqāṣid al-syarī‘ah. This normative legal research applies statutory, conceptual, and Islamic legal approaches to primary and secondary legal materials, which are analyzed descriptively and analytically. The findings show that homologous ART is permissible because the sperm, ovum, embryo, and uterus remain within a valid marital relationship. In contrast, heterologous ART and the use of a surrogate mother involve third parties and create different legal consequences: sperm donation affects paternal lineage, ovum donation creates dual motherhood, embryo donation obscures both parental lines, and surrogacy separates the genetic mother from the gestational mother. From the perspective of maqāṣid al-syarī‘ah, the need to obtain offspring may be classified at the level of ḥājiyyāt, but its fulfillment remains subject to the protection of lineage, life, and property. The novelty of this study lies in its systematic mapping of reproductive elements, parental status, lineage, and inheritance consequences, combined with a staged maqāṣid al-syarī‘ah analysis that balances reproductive benefits against the harms of lineage uncertainty. This study recommends clearer regulation of permitted ART procedures, clinic supervision, biological-origin records, and the protection of children’s identity, family status, and economic rights.